The Effect of Birth Ball on Reducing Labor Pain in The 1st Active Phase at TPMB Wina Julaeli, S.Tr. Keb. Bdn in Labuan District, Banten Province in 2024 - Halimatusyadiah, Leni; Octavia, Rina; Fathiyati, Fathiyati; Giastami, Salma Nur; Rezaldi, Firman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The expulsion of the products of conception after reaching a gestational age of more than 37 weeks, either through a natural process through the vagina (spontaneous vaginal) or through surgical action through the stomach (perabdominal), is referred to as childbirth. This study aims to determine the effect of a birth ball on reducing labor pain during the first active phase at TPMB Wina Julaeli, S.Tr. Keb. Bdn in Labuan District, Banten Province in 2024. This research design is quantitative using the Quasy Experiment research method. The design applied in this research was one group pretest – posttest with 30 respondents and data collection using observation sheets was analyzed using the Wilcoxon test. The result obtained was a significance value of 0.000, which was smaller than the significance result of 5% (p-value = 0.000 < 0.05), therefore the conclusion was that Ha was accepted, which means that there was an influence of the birth ball on reducing labor pain during the first active phase at TPMB Wina Julaeli. S.Tr. Keb. Bdn in Labuan District, Banten Province in 2024. This birth ball therapy can be used during every birth process as an option to reduce pain management for mothers in labor.